2022
DOI: 10.3389/fpsyt.2022.997593
|View full text |Cite
|
Sign up to set email alerts
|

Mapping network connectivity between internet addiction and residual depressive symptoms in patients with depression

Abstract: Background and aimsDepression often triggers addictive behaviors such as Internet addiction. In this network analysis study, we assessed the association between Internet addiction and residual depressive symptoms in patients suffering from clinically stable recurrent depressive disorder (depression hereafter).Materials and methodsIn total, 1,267 depressed patients were included. Internet addiction and residual depressive symptoms were measured using the Internet Addiction Test (IAT) and the two-item Patient He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…68 Compared to bridge symptoms with lower expected influence values, those with higher expected influence values were associated with a higher risk of contagion between different communities of symptoms. 69 Predictability of each node 70 and control of confounding effects in basic demographic data 71 , 72 in the network model were estimated using the R package “mgm”. The value of predictability is indicated as the linkage between its neighboring node.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Compared to bridge symptoms with lower expected influence values, those with higher expected influence values were associated with a higher risk of contagion between different communities of symptoms. 69 Predictability of each node 70 and control of confounding effects in basic demographic data 71 , 72 in the network model were estimated using the R package “mgm”. The value of predictability is indicated as the linkage between its neighboring node.…”
Section: Methodsmentioning
confidence: 99%
“…84 In contrast, another study found that male gender was a risk factor for suicidal thoughts among the general population. 83 Therefore, to examine the inter-relationship between depressive symptoms and suicidality, it is important to minimize the confounding effects caused by basic demographic 72,85,86 the depressive symptoms and suicidality network models, with the structure indexes, were re-evaluated after controlling for age, marital status, gender, and education level (Supplemental Figure S2). Compared to the original network, the re-calculated network model did not find any significant structure change after controlling for the confounding variables (strength: r s = 0.77 [0.54; 0.95]).…”
Section: The Confounding Effects Of Basic Demographic Data On Depress...mentioning
confidence: 99%
“…This offers essential potential targets for relevant intervention measures ( 17 ). In recent years, network analysis has garnered widespread attention and application across various domains of psychology, such as depression ( 18 ), anxiety ( 19 ), acute stress reactions ( 20 ), eating disorders symptoms ( 21 ), and more. Additionally, some items in the Chinese version of the D-RFS may not be suitable for their factor assignments ( 22 ), suggesting the possibility of a better structural model.…”
Section: Introductionmentioning
confidence: 99%
“…Internet addiction can have severe detrimental effects on an individual’s social and physical well-being ( 7 ), including an increased risk of depression and anxiety ( 8 , 9 ), problematic behaviors ( 6 ), poorer academic performance ( 10 ), and severe sleep disorders ( 11 ), and so on. As a result, researchers have investigated various internal and external factors that influence internet addiction and have aimed to uncover its psychological mechanisms in order to develop effective interventions ( 7 , 12–14 ).…”
Section: Introductionmentioning
confidence: 99%